Sort by

- Relevance
- |Time

...c. The system is stable.All roots are on the

**LHS**of the real axis!!2 Answers · Science & Mathematics · 21/04/2011

...)/ (x^2+1)^2 Then multiply all terms by the denominator of the

**LHS**, and equate coefficients for each separate power of x. I admit this...2 Answers · Science & Mathematics · 23/12/2013

...st) ] dt ADD the integral from the RHS to the original integral on the

**LHS**, obtaining: [1 + (a^2/s^2)] * F(s) = 1/s + [(a/s^2)*(sin at)*e^(-st...3 Answers · Science & Mathematics · 11/08/2014

...or particular solution of the complete (non-homogeneous) equation. Try y=sinx , then the

**LHS**: y" + 4y = -sinx +4.sinx = 3sinx so the solution fits! giving the general...3 Answers · Science & Mathematics · 29/12/2012

...x) - cos(x)/sin(x) = tan(x) - cot(x) But now it's perfectly clear that the

**LHS**equals the RHS.1 Answers · Science & Mathematics · 23/04/2013

... obvious, just divide RHS by the bracketed coefficient from the

**LHS**.1 Answers · Science & Mathematics · 25/11/2013

...gal )( 10 gal/min ) dQ/dt = -10Q / 55 Move Q to the

**LHS**and then integrate ∫ 1/Q dQ = -10/55 ∫ dt ln Q = -10t/55...2 Answers · Science & Mathematics · 11/12/2009

...since, 1+any = 1: 1+C =1, 1+B=1 } =AB+A'C =

**LHS**2 Answers · Science & Mathematics · 27/09/2012

... ) x (sin²x + cos²x) =(cos^4) (X) - (sin^4) (x) d)

**LHS**: cot X sin 2X=(cosx÷sinx) x (2sinxcosx) =2cos²x...3 Answers · Science & Mathematics · 07/10/2011

...condition. E.g set a = 0, then b=1 and the value of z = ib = i. The

**LHS**of the given equation is then (-3+i0) of which the absolute value = 3...1 Answers · Science & Mathematics · 05/12/2010